2006
DOI: 10.1063/1.2333692
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alignment in a shock wave

Abstract: Molecular Dynamics simulations of dense nitrogen show that non-spherical molecules have a weak tendency to align their molecular axis such that it lies parallel to the plane of a shock wave front. As a consequence, there is also an even weaker tendency for the molecular rotation axis to align perpendicular to the shock front.The underlying mechanism is discussed and it is argued that this phenomenon can only be observed for dense fluids and only when considering realistic molecular interactions. A single relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…There, it has been found that atoms become confined to planes perpendicular to the velocity gradient. This also sheds a new light on previous results of the authors [12], namely that anisotropic distributions of the molecular orientations are observed in a shock wave, and offers an alternative mechanism underlying this phenomenon.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…There, it has been found that atoms become confined to planes perpendicular to the velocity gradient. This also sheds a new light on previous results of the authors [12], namely that anisotropic distributions of the molecular orientations are observed in a shock wave, and offers an alternative mechanism underlying this phenomenon.…”
Section: Discussionmentioning
confidence: 68%
“…A more complete table and plots of the averaged shock structure can be found in Refs. [12] & [7]. The pressure and the speed of sound do not follow directly from our MD results, but are calculated from reference-type empirical equations of state suggested by the National Institute of Standards and Technology (NIST) [13,14].…”
Section: B Correlation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The angular momentum only becomes significant because it determines the location of the atoms subsequently. We have proposed [10] a nondimensional parameter governing the magnitude of the anisotropy, which includes the elongation of the molecule, the magnitude of the density gradient, the density, and the curvature of the potential function between molecules. Additional simulations with different flow conditions are required to confirm this scaling.…”
Section: Anisotropic Molecular Orientationsmentioning
confidence: 99%
“…4 through 7 will then discuss one phenomenon which has only recently come to light (see Refs. [10][11][12], respectively, for more details). These are all aspect of a broader research project carried out over the last several years at ETH Zurich [13].…”
Section: Introductionmentioning
confidence: 99%